The Role of Farmer Groups in The Development of Rice Farming in Warnasari Village, Tamban Catur District, Kapuas Regency: A Descriptive Analysis - Suyatno, Suyatno; Nurlaela, Siti; Widiarso, Budi Purwo (JSEP (Journal of Social and Agricultural Economics), 2024)
This study aims to determine the role of farmer groups in the development of rice commodity farming in Warnasari Village, Tamban Catur Subdistrict, Kapuas Regency. This study used the deskriptif quantitative method which was carried out from August to December 2022. The selection of village subdistricts and farmer groups was carried out proposively, while the sampling of respondent farmers used proportional random sampling. The type of data used is primary data and skunder data as supporting data. The results of data analysis showed that the role of farmer groups in the development of rice farming in Warnasari Village as a learning class was categorized as medium with a value of 69.2%, the role of farmer groups as a vehicle for cooperation was also categorized as medium with a value of 60.8%, while the role of farmer groups as production units was categorized as high with a value of 78.5%. After obtaining the results of the research, it was recommended to farmer groups to increase group activities that are mutual assistance, for example during â€œgropyokanâ€, rat control, and other pest control to increase farmer participation and responsibility, thus it was hoped that the role of farmer groups as a vehicle for cooperation can be increased.